Testing the reliability of fading correction methods for feldspar IRSL dating: A comparison between natural and simulated-natural dose response curves. (15th December 2018) - Li, Yan; Tsukamoto, Sumiko; Long, Hao; Zhang, Jingran; Yang, Linhai; He, Zhong; Frechen, Manfred
Abstract: The reliability of the fading correction methods for feldspar infrared stimulated luminescence (IRSL) dating in the non-linear part of the dose response curve proposed by Wallinga et al. (2007) (modified after Lamothe et al., 2003) and Kars et al. (2008) was evaluated using samples from the Chinese loess-palaeosol sequence in Luochuan with the reference ages. Two protocols, the post-infrared (IR) IRSL at 225 °C (pIRIR225 ) and the pulsed IR at 50 °C, were applied in this study. The natural dose response curve (DRC) for the IR50 (pre-pIRIR225 ), pIRIR225 and pulsed IR50 was first constructed. The simulated-natural DRC and the fading corrected ages were then determined. The characteristic saturation dose ( D 0 ) of the simulated-natural DRC was found to be larger than that of the natural DRC for the IR50 (pre-pIRIR225 ) and pIRIR225 signals, whilst the two D 0 values agreed with each other for the pulsed IR50 . The saturation ratio ( n/N ) of the simulated-natural DRC agreed with the natural one within 10% uncertainty for all three signals. The fading corrected ages using these two methods agreed with the reference ages, confirming the reliability of the two fading correction methods. However, our numerical simulation on the fading correction showed that the method of Wallinga et al. (2007) significantly overcorrect ages when the fading rates are larger than ca. 4–5%/decade. Highlights: The saturation ratio (n/N) of the simulated DRC agreed with the natural one with 10% uncertainty for all three signals. Both the Kars et al. (2008) and Wallinga et al. (2007) methods provides reliable fading corrected ages. The corrected ages after Wallinga et al. (2007) overestimate those after Kars et al. (2008) for g of >ca. 4–5%/decade..